Health in the Americas -2002- (PAHO WashingtonUS, 2002)
Analyzes the health situation and trends in the region of the Americas. Describes the current status and trends in health promotion, environmental health, disease prevention and control, availability of health resources and technology, and external cooperation in health. Presents the most up-to-date health situation analysis for each of the 48 countries and territories of the Americas.
Documentation Centre has: 2002; 2012